Strategi Bisnis Asuransi Kendaraan Bermotor PT. Asuransi Jasa Indonesia - , Hendi Pratama ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Asuransi Jasa Indonesia (Persero) is a State Owned Insurance as one of the largest general insurance in Indonesia. In 2010 PT. Asuransi Jasa Indonesia (Persero) has increased premiums up to 2890 billion rupiahs, which place PT. Asuransi Jasa Indonesia as the second position in national general insurance business, but the growth is not in line with the gross premium of auto insurance industry that recorded a premium income of 356 billion, which is place only the sixth position in vehicle insurance industry. PT. Asuransi Jasa Indonesia (Persero) recorded a net profit of 194 billion rupiahs, which occupies the fifth position in the general insurance industry. The Intense competition in the auto insurance industry can be seen by the small amount of PT. Asuransi Jasa Indonesia (Persero) market share in the market. PT. Asuransi Jasa Indonesia (Persero) is having a main issue with this particular Class of Business, therefore a company primarily needs to formulated an precise and effective strategies to puzzle out the problems. There are three main purposes of this research